The Relationship Between Adequate Housing And Household Sanitation With The Success Of Tuberculosis Patient Treatment In Semarang City - Abdul Hakam, Mochamad; Diken Safitri, Baiq; Dessita Wandastuti, Anggun; Farid Husni, Muhammad; Wilson Setiawan, Andreas; Rahel Konoralma, Amanda; Lumban Radja, Benny; Setiono, Oki; Ratna Wulan, Widya (Health Science UDINUS, 2024)
Tuberculosis is a global health problem, including in Semarang City. There were 7,844 cases in 2023 in Semarang City. The success rate of treatment in Semarang City is still at 85%. Tuberculosis is closely related to environmental factors and housing quality. This study examined how adequate housing and household sanitation conditions for Tuberculosis patients are linked to their treatment success. Data on the housing and household sanitation of the patients were taken in the first quarter of 2024 based on home visits to drug-sensitive Tuberculosis patients domiciled in Semarang City who were diagnosed in 2023 and 2024 who were still undergoing treatment and the final results of their treatment were seen in the last quarter of 2024. The data were analyzed using linear regression to examine the relationship between adequate housing and patient treatment success and the link between household sanitation and the treatment outcomes of Tuberculosis patients in Semarang City. Of the 2,007 samples, 789 patients, or 39.3%, were children (aged <15 years), and 1,119, or 55.8%, were male. It was found that 1,023 (50.9%) patients had inadequate houses, and 1,113 (55.5%) patients had poor household sanitation. The results showed that 119 (5.9%) patients recovered, 873 (43.5%) patients completed treatment, 27 (1.3%) patients died, 96 (4.8%) patients dropped out of treatment (lost to follow-up), and 4 (0.2%) patients failed. There was a significant association between housing adequacy and patient treatment outcomes (p = 0.042). Household sanitation does not show a significant relationship with treatment success (p-value = 0.564). There are still other factors that can affect the recovery of Tuberculosis patients. It is better to involve political, social, economic, and cultural sectors in addition to the health sector to carry out interventions to improve the adequacy of housing for Tuberculosis patients.